Development of an Ethnoscience Based E-Module on the Diversity Material of Medicinal Plants of the Bugis Tribe - Apriansyah, Muhammad Ansar; Syarif, St. Humaerah; Anugra, Novia; Nikmatullah, Muhamad (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2024)
Advancements in educational technology demand the use of electronic learning media that still prioritize local potential. The aim of this research is to determine the steps for developing, validity and practicality of an ethnoscience-based e-module on the biodiversity of medicinal plants of the Bugis tribe. This research is development research (R&D) adopting the ADDIE development model. Data analysis techniques consist of quantitative descriptive analysis and qualitative descriptive analysis. Based on the research and development results, the validity percentage of the e-module was obtained: 85.27% by material validator I, 94.74% by material validator II, 84% by media validator I, 90% by media validator II, and 86.67% by the language validator, categorized as 'Highly Valid.' The practicality test of the e-module, obtained from teacher responses, was 86.25% and from student responses, 90.62%. The developed product is categorized as Practical and suitable for use.ABSTRAK: Kemajuan di bidang teknologi pendidikan menuntut digunakannya media pembelajaran elektronik yang tidak meninggalkan potensi lokal. Tujuan penelitian ini adalah untuk mengetahui langkah pengembangan, kevalidan, dan kepraktisan e-modul berbasis etnosains pada materi keanekaragaman hayati tumbuhan obat suku Bugis. Penelitian ini merupakan penelitian pengembangan (R&D) dengan mengadopsi model pengembangan ADDIE. Teknik analisis data terdiri atas analisis deksriptif kuantitatif dan analisis deksriptif kualitatif. Berdasarkan hasil penelitian dan pengembangan diperoleh data persentase kevalidan e-modul yaitu sebesar 85,27% oleh validator materi I, 94,74% oleh validator materi II, 84% oleh validator media I, 90% oleh validator media II, dan 86,67% oleh validator Bahasa, dengan katagori “Sangat Valid”. Untuk uji kepraktisan e-modul diperoleh dari respon guru sebesar 86,25% dan respon siswa sebesar 90,62%. Kategori produk pengembangan Praktis dan layak untuk digunakan.